Timbel Raos Catering Business Development Using Break-Even Analysis - Chiessa Baihaqy; Nababan Nicholas; Agatha Rinta Suhardi (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
Tight culinary business competition and fluctuations in food prices as the main ingredients of the catering business affect the determination of food selling prices. The ability to manage operational costs effectively and set competitive selling prices are determining factors for long-term business success. The main problem in small culinary industry businesses is the difficulty in calculating the break-even point needed to determine the number of units or income needed so that the catering party does not experience a loss. This research is related to the home catering business which is a small business that has the potential to develop into a medium and large business. The research method used is descriptive analysis and calculations using the break-even point formula. Timbel Raos Catering will gain profit by selling at least one package of chicken rice and fried food. The use of break-even analysis helps home business development in finding the minimum amount of product sales so that capital returns can run smoothly and capital can continue to circulate.